Sanksi Bagi Mantan Terpidana Kejahatan Seksual Pada Anak - Herminiastuti Lestari (Pusat Riset dan Inovasi Nasional, 2022)
The public's reaction to the rousing welcome from the former convict of sexual crimes against children with the initials SJ got a lot of attention. Sexual crimes against children which are special crimes have special treatment, both as victims and perpetrators. Because of its specificity, there is a separate treatment starting from the investigation, trial, sanctions, sentencing, also post-trial.After sentencing, the perpetrators are not automatically able to move freely in public, so that when a former convict appears in public, there is a reaction from the public. Normically or socially there is a restriction for former convicts of sexual crimes. This is related to the ethics that apply in society where sexual crime is an immoral act against children that should be protected by all parties, be it society, institutions or the government. Because it is related to the morals of the immoral act, the burden borne by the victim psychologically will affect the future of the child, so that the perpetrator of the crime cannot be accepted immediately to appear in public, thus causing sanctions after completion of sentencing